PROFIT SHARING DAN INVESTASI DEPOSITO MUDHARABAH DALAM PERSPEKTIF FINANCING TO DEPOSITE RATIO - Dadan Ramdhani (FEB Universitas Sultan Ageng Tirtayasa, 2017)
This research of the deposit mudharabah in order to determine the effect of the level of profit-sharing and financing to deposite ratio to deposite mudharabah. The data used in this research is secondary data and times series obtained from the Financial Statements of Bank Indonesia publications, and reports Islamic banks are concerned. Sampling technique used was purposive sampling. The sample in this study were 48 Islamic banks the financial statements of the years 2007-2010. Data analysis techniques used in this study is the multiple linear regression analysis. These results indicate that the variable rate for the results show a significant effect on mudharabah deposits. FDR variables no significantly influence mudharabah deposits.